Unemployment among younger and older individuals: does conventional data about unemployment tell us the whole story? - Hila Axelrad; Miki Malul; Israel Luski (Journal for Labour Market Research, 2018)
In this research we show that workers aged 30-44 were significantly more likely than those aged 45-59 to find a job a year after being unemployed. The main contribution is demonstrating empirically that since older workers' difficulties are related to their age, while for younger individuals the difficulties are more related to the business cycle, policy makers must devise different programs to address unemployment among young and older individuals. The solution to youth unemployment is the creation of more jobs, and combining differential minimum wage levels and earned income tax credits might improve the rate of employment for older individuals.
Keywords: J64; J68; 330; Unemployment; Employment; Aging; Older workers; OECD